Profitability analysis of normal season and off-season muskmelon cultivation in district Sialkot, Pakistan - Muhammad Latif; Falak Sher; Muzzammil Hussain (Innovations in Agriculture)
A field survey was conducted during 2016 to estimate the profitability of normal season and off-season muskmelon cultivation in district Sialkot, Pakistan. The primary data was collected from forty farmers with convenience sampling method. Economic parameters like net return and BCR were employed. Off-season muskmelon cultivation was found economically feasible due to additions of yield (17%), gross income (122%), profit (161%) and market price (90%) in comparison to normal season crop. Therefore, it is recommended to cultivate the off-season muskmelon (BCR 3.26) to obtain more profit and fulfill the customer demand in less supply period instead of normal season cultivation (BCR 2.44).